Import Price Uncertainty and the Distribution of Income - Appelbaum, Elie; Kohli, Ulrich (The Review of Economics and Statistics, 1997)
In this paper we estimate oil and nonoil import demand functions for the United States under the assumption that import prices are uncertain. Both import demand functions are formally derived from an expected utility maximization problem, treating imports as inputs to the technology. The model allows us to test for risk aversion and to assess the impact of uncertainty on the volume of imports, gross output, and the distribution of income. We find that uncertainty leads to a reduction in welfare, imports, and gross output. Moreover, it hurts labor relatively much more than capital. The impact of uncertainty, however, is found to be quite small.